2023
DOI: 10.1021/acs.joc.3c00248
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dehydrogenation-Triggered Selective C3-Alkylation of Indoles by Homogeneous Azo-aromatic Cobalt Catalysts

Abstract: Herein, we report azo-benzimidazole containing cobalt complexes (1−3) for alcohol dehydrogenation-triggered C3-alkylation of indoles. In complexes 1−3, ligands are redox noninnocent and showed facile irreversible L/L • reduction followed by Co(II)/Co(I) reduction in close-lying potentials. Taking advantage of facile redox events in 1−3, the first aerial dehydrogenation of alcohols to their corresponding carbonyl compounds is explored. Subsequently, C3-alkylation of indole was studied using alcohols as the alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The ligands, L 1–3 as well as complexes, 1 – 3 (Table , Scheme S1) used in this work were synthesized following our previous report . A schematic representation of ligands, L 1–3 and complexes, 1 – 3 are shown in Table and Scheme S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligands, L 1–3 as well as complexes, 1 – 3 (Table , Scheme S1) used in this work were synthesized following our previous report . A schematic representation of ligands, L 1–3 and complexes, 1 – 3 are shown in Table and Scheme S1.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we have observed that alcohol oxidation and subsequent C3-alkylation of indole proceeded through a radical pathway where the coordinated azo-pyridine ligand acted for the α-CH bond activation of alcohols . To probe this event further in this reaction, we examined the C9-alkylation of fluorene with 3-methoxybenzyl alcohol in the presence of the TEMPO radical.…”
Section: Resultsmentioning
confidence: 99%
“…This observation has been further applied in the catalytic oxidation of alcohols to generate the corresponding carbonyls, the latter being involved in the cascade synthesis of C-3 alkylated indoles (Scheme 19), via an alkylideneindolenine intermediate. 114 The catalytic reaction mechanism is depicted in Scheme 20 where the metal–ligand cooperative redox transformation has been exemplified and the formation of cobalt( i ) from cobalt( ii ) during the catalytic cycle has been confirmed by EPR as well as XPS studies. The scope of the catalysis is presented in Schemes S11–S13 †…”
Section: Types Of Catalysts Catalytic Pathways and Scope Of Catalysismentioning
confidence: 98%
“…Complexes with a pincer-like ligand has been found to be beneficial for such alcohol dehydrogenation triggered synthesis of compounds. A phosphine donor ligand containing ruthenium complexes was very effective in this purpose . However, other 4d -metals like palladium, rhodium, and iridium complexes were also explored for the synthesis of quinolines. Notably, these kinds of metals are expensive and less earth abundant. , Currently, efforts are ongoing to develop efficient catalysts using cheap and earth-abundant 3d -transition metal complexes. Recently, complexes with nitrogen donor pincer ligands, particularly complexes having a redox non-innocent ligand with 3d -transition metal ions, have been found to be very effective for catalytic application. It has been observed that the redox non-innocent ligand containing complexes can generate a metal-stabilized organic radical that can lead to such dehydrogenation catalysis efficiently and selectively under a milder reaction condition. , Herein, we report an efficient, economical, and cheap synthetic strategy toward the synthesis of 2-substituted quinoline derivatives employing non-innocent amine functionalized azo-aromatic pincer-like complexes of cobalt where the dehydrogenation of alcohol occurs via a ligand-based redox event (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been observed that azo-aromatic transition metal complexes catalyze the dehydrogenation reactions of alcohols in significantly milder conditions . Thus, we became interested to explore the catalytic efficiency of complexes 1 – 4 for the dehydrogenation of 2-amino benzyl alcohol for the synthesis of quinoline.…”
Section: Introductionmentioning
confidence: 99%